While justice sleeps : a novel - Abrams, Stacey (Doubleday, 2021)
"An inside-Washington thriller about an ambitious law clerk thrown into a life-or-death treasure hunt with major national implications when the Supreme Court justice she works for slips into a sudden coma"--